PENGARUH PEMBERIAN PUPUK GUANO TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) PADA DUA METODE VERTIKULTUR - Tutik Nugrahini (DINAMIKA PERTANIAN, 2013)
ABSTRACT The purpose of this study was to determine the effect of guano fertilizer and methods verticulture and their interactions on the growth and yield of lettuce, and to find the guano fertilizer dose and proper verticulture method for lettuce. The experiment was conducted in Pinang Mas Housing Complex RT 46 Sempaja Village, North Samarinda sub district of Samarinda Cityfrom July 2011 to September 2011. The Split Plot Design within Randomized Block Design was used with 3 repitions. Factor of verticulture methods as main plots (V) consisted of a vertical (v) and horizontal (v2); Factor of guano fertilizer as sub-plots (G) consistied of: no fertilizer guano application (g0), 1 Mg ha-1 or 2 kg pots-1 (g1), 2 Mg ha-1 or 4 kg pots-1 (g2), and 3 Mg ha-1 or 6 kg pots-1 (g3). Analysis of the data used analysis of variance followed by least significant difference test at 5% significance level. The results showed that vertical and horizontal methods verticulture had no a significant effect on the all parameters observated. Guano fertilizer treatments affected significantly on plant height and number of leaves at the age of 10, 20, and 30 days after planting, plant fresh weight, and organoleptic tests of the color of the leaves and the level of crispness. The highest plant fresh weight wasproduced by treatment 3 Mg ha-1 or 6 kg pots-1 with 94.50 g fresh weight; The interaction between the methods of guano fertilizer verticulture had no a significant effect on the observed parameters: The organoleptic test by panelists provided a light green leaf color, crisp and rather liked.